Tasawuf Sebagai Pilihan Menuju Kebenaran : Kajian Pemikiran Al-Ghazali - Baedhowi Baedhowi (Millah: Journal of Religious Studies, 2003)
This article tries to trace al-Ghazali’s thought on Sufism. According to the writer, for al-Ghazali, Sufism is a final choice and the last way in his life. Before studying Sufism, al-Ghazali has studied many kinds of Islamic knowledge such as kalam, Fiqh, batiniah etc. But all of them could not satisfy his intellectual needs. Finally, he studies the Sufism seriously, that he claimed as the most ultimate truth. Awakening of al-Ghazali’s Sufism is because of by some historical backgrounds (historical settings). In his life, Syi’ah and Sunni want to dominate each other in ideology and Islamic discourses. The position of al-Ghazali’s thought is in Ahl Sunnah and to defend their teachings. For this reason, to study and to explore al-Ghazali’s Sufism, we must conduct historical deconstructions. To actualize al-Ghazali’s thought on Sufism, we can study multidisciplinary approach, a new methodology and epistemology that relating to modernity.